Analisis Pengaruh Likuiditas, Ukuran Perusahaan dan Leverage Terhadap Profitabilitas pada Perusahaan Sektor Agriculture yang Terdaftar di BEI Periode 2020- 2024 - Putri, Della Amaliyah; Makmur, Makmur; Anwar, Arfianti Novita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to analyze the effect of liquidity, firm size, and leverage on profitability in agriculture sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Profitability, measured by Return on Assets (ROA), reflects a company’s ability to generate earnings from its total assets and serves as a key indicator of financial performance. Liquidity is proxied by Current Ratio (CR), firm size is measured using the natural logarithm of total assets, and leverage is represented by Debt to Asset Ratio (DAR). Materials and methods. This research employed a quantitative approach using secondary data derived from annual financial reports published on the official website of the Indonesia Stock Exchange. The population consisted of 22 agriculture sector companies, with 10 companies selected as samples through purposive sampling based on predetermined criteria. Data analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression analysis supported by SPSS software. Hypothesis testing included the coefficient of determination (R²), t-test, and F-test at a 5% significance level. Results. The results indicated that liquidity has a positive and significant effect on profitability. Firm size and leverage, however, do not have a significant partial effect on profitability. Simultaneously, liquidity, firm size, and leverage significantly influence profitability. The adjusted R² value of 0.160 shows that 16% of the variation in profitability is explained by the model, while 84% is influenced by other factors outside the research variables. Conclusions. The findings highlight that liquidity stability is a more dominant determinant of profitability in the agriculture sector compared to firm size and leverage. Effective working capital management is therefore crucial to maintaining sustainable financial performance.